2020
DOI: 10.1021/acs.molpharmaceut.9b01167
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles containing a combination of a drug and an antibody for the treatment of breast cancer brain metastases

Abstract: In women with human epidermal growth factor 2 (HER2)-positive breast cancer, improved control of systemic disease with new therapies has unmasked brain metastases that historically would have remained clinically silent. Efficacy of therapeutic agents against brain metastases is limited by their inability to permeate the blood-brain and blood-tumor barriers (BBB and BTB) in therapeutic amounts. Here, we investigate the potential of mucic acid-based, targeted nanoparticles designed to transcytose the BBB/BTB to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Indeed, albumin nanoparticles demonstrated increased delivery of lapatinib to BrM in animal models, thereby inhibiting the growth of metastases and extending survival 61 . Combination therapies have also been attempted with nanoparticle delivery, including a chemotherapy plus anti‐HER2 antibody combination, which reduced tumor volume in an intracranial HER2+ model 62 …”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, albumin nanoparticles demonstrated increased delivery of lapatinib to BrM in animal models, thereby inhibiting the growth of metastases and extending survival 61 . Combination therapies have also been attempted with nanoparticle delivery, including a chemotherapy plus anti‐HER2 antibody combination, which reduced tumor volume in an intracranial HER2+ model 62 …”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Nanoparticle technology has also been explored as a method to increase BrM exposure to HER2-targeting agents.Indeed, albumin nanoparticles demonstrated increased delivery of lapatinib to BrM in animal models, thereby inhibiting the growth of metastases and extending survival 61. Combination therapies have also been attempted with nanoparticle delivery, including a chemotherapy plus anti-HER2 antibody combination, which reduced tumor volume in an intracranial HER2+ model 62. There is growing appreciation for the need of combination therapies in HER2+ BCBrM, as HER2-directed therapy alone does not appear to always be sufficient.…”
mentioning
confidence: 99%
“…This defence system is a unique problem which prevents majority of the current therapies from succeeding. Utilising lipid-soluble cargoes such as nanoparticles which disintegrate at the target site ( 215 , 216 ), or focused ultrasound techniques e.g., pulsed ultrasound ( 217 ), can greatly improve the delivery of targeted drugs.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…These NPs also enabled controlled drug release, as pH-responsive portions of the MAP-CPT complex are cleaved due to acidification during transcytosis, releasing CPT into the brain. The same group assessed the ability of this BBB-targeting MAP delivery system to deliver trastuzumab alone or in combination with CPT [145]. Importantly for IT, which includes ICI therapeutic antibodies, this strategy was feasible for antibody delivery and found that BBB-targeted MAP-CPTtrastuzumab combination NPs result in significantly better tumor control than either therapy alone.…”
Section: Bbb Targeting and Translocation Strategiesmentioning
confidence: 99%